Doctoral Education for the Knowledge Society Convergence or Divergence in National Approaches? (Knowledge Studies in Higher Education,, 2018)
This book explores and compares the systems of doctoral education in twelve higher education systems, consisting of four systems in East Asia, four in Europe and four Anglo-American systems. The emphasis placed on doctoral education and training has increased dramatically in many higher education systems in response to the global competition for highly skilled human resources to serve the needs of knowledge societies. Doctoral education is a key element within the research and development infrastructure, and doctoral students support university research and represent the next generation of the professoriate. While doctoral education has received considerable attention within national higher education systems, there has been surprisingly little international or comparative research on the structure of doctoral education and the nature of contemporary reforms. .